A paradigm shift in collaborative learning: Insights from the theory of collaborative advantage for inclusive and engaging pedagogical design - Verster, B. (South African Journal of Higher Education, 2024)
Collaborative or group work is a widely-used learning strategy in undergraduate studies, yet it is often met with resistance. Previous research on the topic identified the complexity of collaborative learning strategies as a significant concern for both instructors and students. In response, this paper employs the theory of collaborative advantage (and collaborative inertia) to explore a longitudinal learning event and illuminate the complexities and advantages which students might encounter. Based on the case study method, the paper presents four pedagogical design propositions: (1) design for co-constructing goals, (2) learning-support frameworks as magnifiers, (3) attentiveness to culturally diverse voices, and (4) learning designed for power dynamics. It is argued that these design propositions can assist in fostering collaborative awareness in various disciplines and subject areas.